2000
DOI: 10.1128/jvi.74.5.2288-2292.2000
|View full text |Cite
|
Sign up to set email alerts
|

JC Virus Enters Human Glial Cells by Clathrin-Dependent Receptor-Mediated Endocytosis

Abstract: The human polyomavirus JC virus (JCV) is the etiologic agent of a fatal central nervous system (CNS) demyelinating disease known as progressive multifocal leukoencephalopathy (PML). PML occurs predominantly in immunosuppressed patients and has increased dramatically as a result of the AIDS pandemic. The major target cell of JCV infection and lytic replication in the CNS is the oligodendrocyte. The mechanisms by which JCV initiates and establishes infection of these glial cells are not understood. The initial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
190
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(203 citation statements)
references
References 26 publications
5
190
0
5
Order By: Relevance
“…30,[35][36][37] However, we did not appreciate any evidence of clinical improvement despite ziprasidone-inducing significant sedative side effects. These findings raise the question whether higher doses, than clinically tolerated, are required to achieve a beneficial effect.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…30,[35][36][37] However, we did not appreciate any evidence of clinical improvement despite ziprasidone-inducing significant sedative side effects. These findings raise the question whether higher doses, than clinically tolerated, are required to achieve a beneficial effect.…”
Section: Discussionmentioning
confidence: 76%
“…or intrathecally), cidofovir i.v., alone or in combination, and withdrawal of immunosuppression medications. Pho et al 35 showed that the neuroleptic drug, chlorpromazine, inhibits the endocytic pathway used by JC virus to infect glial cells. Atwood.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological findings are remarkably similar to SV40 and murine polyoma virus host cell entry. This is in contrast to the manner of entry of JC virus, that has been found to enter cells by following the usual endocytic pathway using clathrin-coated vesicles (20). The different pathways of viral cell entry do not appear to directly correlate with the type of receptor, since BK, JC and murine polyoma viruses have sialic-acid type receptors, whereas SV40 has receptors related to the MHC system (30).…”
Section: Discussionmentioning
confidence: 83%
“…Specific functional and molecular studies on the biological behavior of BK virus at the cellular level are not available, and very little is known about the interactions between the virus and the host cells. In contrast, numerous studies have characterized the cellular interactions of the SV40 virus and murine polyoma virus (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). For the purpose of further understanding the pathogenicity of BK virus, it may be helpful to draw potential analogies with these better known polyoma viruses, particularly the SV40.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation